Rol de enfermería y aplicación de reanimación cardiopulmonar en paciente intraoperatorio - Ortega Álvarez, Alexander Mauricio (Machala : Universidad Técnica de Machala, 2023)
Introduction: Intraoperative cardiorespiratory arrest (CPA) is determined as the abrupt, unexpected interruption of cardiac output and ventilation, for which a (CPA) is given during admission to the operating room, during the application of anesthesia or 60 minutes after completion. sedation; Given this complication, it is determined that intraoperative cardiopulmonary resuscitation (CPR) is a technique which involves a series of sequential maneuvers that are intended to achieve patient survival. It is important that the nursing staff is trained both scientifically and technically, to attend CPR, therefore the instrumentalist must be with a proactive conduct and lead the work team for timely care, in a person who presents a cardiopulmonary arrest in order to reduce mortality and sequelae that can be generated. Objective: To describe the role of the nursing professional in cardiopulmonary resuscitation in intraoperative patients, identifying altered functional patterns according to Marjory Gordon's theory, for which the Nursing Care Process (PAE) is designed. Methodology: The methodology applied in this research was a qualitative study. descriptive, analytical by searching for information in different web browsers such as: Scielo, Dialnet, Pub-Med, Redalyc. Conclusion: In the present research topic, the role of nursing in the presence of a patient with intraoperative cardiorespiratory arrest was described, it was possible to identify the altered patterns in the patient, allowing nursing professionals, both the circulating nurse and the scrub nurse, to act with a proactive behavior.
Introducción: La parada cardiorrespiratoria (PCR) intraoperatoria es determinada como la interrupción abrupta, imprevista del gasto cardiaco y de la ventilación, por la cual una (PCR) se da durante su ingreso a quirófano, en la aplicación de la anestesia o 60 minutos culminada la sedación; ante esta complicación, se determina que la reanimación cardiopulmonar (RCP) intraoperatoria, es una técnica la cual implica una serie de maniobras secuenciales que tienen la finalidad de lograr la supervivencia del paciente, Es importante que el personal de enfermería esté capacitado tanto científica como técnica para atender RCP, por consiguiente la instrumentista debe estar con una conducta proactiva y liderar el equipo de trabajo para una atención oportuna, en una persona que presente una parada cardio pulmonar con la finalidad de disminuir la mortalidad y secuelas que pueden generar. Objetivo: Describir el rol del profesional de enfermería en la reanimación cardiopulmonar en pacientes intraoperatorios identificando los patrones funcionales alterados según la teoría de Marjory Gordon para lo cual se diseña el Proceso de Atención de enfermería (PAE). Metodología: La metodología aplicada en la presente investigación fue un estudio de tipo cualitativa. descriptiva, analítica mediante la búsqueda de información en los diferentes buscadores web como lo son: Scielo, Dialnet, Pub-Med, Redalyc. Conclusión: En el presente tema de investigación se describió el rol de enfermería ante un paciente con paro cardiorrespiratorio intraoperatorio, se logró identificar los patrones alterados en el paciente, permitiendo a los profesionales de enfermería tanto el enfermero circulante e instrumentista actuar con una conducta proactiva.
Keywords: ROL DE ENFERMERIA; PARO CARDIORRESPIRATORIO; REANIMACION CARDIOPULMONAR